PREPARING FOR AN ENGLISH-LANGUAGE JOB INTERVIEW: STRATEGIES FOR BOTH RECENT GRADUATES AND THOSE WITH MORE EXPERIENCE - Dezas Perdani, Yella (SEEIJ (Social Economics and Ecology International Journal), 2023)
Job seekers typically must traverse some stages during the job search process. A job interview is one of the crucial steps in the job application process. One of the series was picked up. Job interviews, or what is also known as job interviews, are currently an integral part of the hiring and selection process. The validity of interviews is somewhat lower than tests, such as psychological tests, which can provide a direct overview of job applicants. Nevertheless, interviews offer several benefits that make life easier for employers, particularly selection officers. In addition, job candidates benefit from this interview because they can explain themselves directly, increasing their chances of converting a job vacancy into a job offer. Currently, the Indonesian economy is expanding, and in response to the global market and the 4.0 era, many foreign firms are investing and constructing businesses in Indonesia. Workers from Indonesia must enter these foreign companies and assist with all necessary processes. Furthermore, interviews in English are unavoidable because English, also known as the international language, is commonly used by foreign companies to recruit employees. Therefore, job applicants must prepare for English-language interviews. It encourages the writer to assist prospective job applicants in preparing for job interviews, particularly those conducted in English. This Community Service Activity (PKM) is intended to prepare job applicants, particularly English-speaking job interviews, to pass the selection process. Thus, it is anticipated that this training will contribute to the preparation of job applicants before their application.